PERILAKU ELEKTRAL WARGA NU TRANGGALEK DI ERA POLITIK DINAMIS: STUDI KASUS AFILIASI NU DENGAN PKS - Agus Cahyono; Akhmad Rizqon Khamami; Teguh Teguh (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to comprehensively understand the electoral behavior of Nahdlatul Ulama (NU) members in Trenggalek in the context of the affiliation of some of them with the Prosperous Justice Party (PKS), amidst increasingly fluid and pragmatic political dynamics. Specifically, this study analyzes the factors that drive the association of NU members with PKS, describes PKS's political strategy in embracing NU's traditional base, and examines the implications of this affiliation for the future of Islamic politics in Indonesia. This study uses the methodSystematic Literature Review (SLR)by collecting 21 scientific articles and contextual data from relevant studies, including media analysis, voter behavior surveys, and party documents. The results of the study indicate that this affiliation is driven by disappointment with traditional NU parties such as PKB, the strong work ethic of PKS cadres at the grassroots, an adaptive socio-cultural approach, and perceptions of PKS's political integrity. These findings also indicate the emergence of a new pattern in the political behavior of NU members that is more pragmatic and oriented towards concrete benefits. In conclusion, this phenomenon reflects changes in the increasingly plural and open political map of Islam in Indonesia. The implication is that Islamic-based organizations and parties need to build new strategies to maintain relevance amidst dynamic changes in voter orientation